The Generation of an Antibody to the Bearded-Ear Protein in Maize - Bland, Jessica (East Carolina University, 2019)
Flowers are essential for plants to reproduce and also produce seeds and fruits that are consumed as food. Zea mays (maize) is both a staple crop and serves as a model for other grass species. In maize, male and female flowers are present on separate inflorescences; the ear holds the female flowers and the tassel holds the male flowers. To understand the normal function of genes in maize development, we study mutants that affect development of one or both inflorescences. My project focuses on the bearded-ear (bde) gene. bde mutants have multiple floral defects and are female sterile. In the ear, bde mutant flowers make extra floral organs and, in the tassel, flowers often contain silks. bde encodes a MADS-box transcription factor; MADS-box transcription factors have well-known roles in floral development in diverse species. The long-term goal of my project is to develop tools which can be used to express recombinant protein in bacteria. This recombinant protein could be used as an antigen to generate a BDE-specific antibody that could be used to further investigate the function of the BDE protein in a number of downstream applications, such as chromatin immunoprecipitation coupled with next-generation sequencing (ChIP seq) and immunoprecipitation coupled with mass spectrometry (IP Mass Spec).
Keywords: cloning, antibody, maize